Contrast Agent Incorporation into Silicone Enables Real‐Time Flow‐Structure Analysis of Mammalian Vein‐Inspired Soft Pumps. (25th February 2015) - Loepfe, Michael; Schumacher, Christoph M.; Burri, Cornelia H.; Stark, Wendelin J.
Abstract : The construction of machines consisting essentially of soft parts is a nascent and multidisciplinary research field between material science, machine engineering, and robotics. Soft silicones represent a promising class of materials for the creation of a vast multitude of biologically inspired entities. In the present work, a new type of mammalian vein‐inspired soft silicone pump is introduced and characterized, which is fabricated by virtual lost‐wax casting of 3D‐printed injection molds. These pumps can be actuated pneumatically or by internal gas combustion and preserve their functionality even after a freezing/unfreezing cycle. The possibility of using medical examination methods such as ultrasonic imaging to directly access flow information inside soft pumps is shown. Based on soda lime glass microspheres, a method is demonstrated to enhance contrast properties during such color online Doppler imaging for a detailed understanding of the inner fluid‐structure interactions. Abstract : There is a nascent research field on machines that are made essentially from soft materials. A new type of mammalian vein‐inspired soft silicone liquid pump is presented and characterized, that is based on lost‐wax casting of 3D printed injection molds. By functionalizing the material with contrast agents, inner workings can be visualized in real‐time by the use of medical ultrasonography.